Direct synthesis of ordered mesoporous carbon applied in hydrogen storage - Juárez, Juliana María; Gómez Costa , Marcos Bruno; Anunziata, Oscar Alfredo (Springer Science+Business Media, 2018)
In this work, we present a direct, novel and low cost method for the preparation of an ordered mesoporous carbon (OMC). OMC was successfully synthesized by the carbonization of the silica/triblock copolymer/sucrose composite in the presence of sulfuric acid. The resulting material was characterized by XRD, N2 sorption analysis and TEM techniques. The novel synthesis technique improved significantly the H2 storage properties (3.78 wt%) compared with that of CMK-3 synthesized using the nanocasting strategy (2.2 wt%) at 77 K and 10 bar.
Keywords: Carbon materials; Hydrogen storage; OMC; Nanomaterials